THE IMPLEMENTATION OF RISK BASED AUDIT IN PT. PUPUK KALIMANTAN TIMUR - Nurfiani, Sarah Erlinda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Risk based audit has been gaining importance in recent years. Lately, risk based audit has been consider as an effective method to the business environment that always changing. The objective of this research is to know the implementation of risk based audit in PT. Pupuk Kalimantan Timur, likewise the weakness and strength. Qualitative method was used in this research. Therefore, the guidance in this research is the author's interpretation. Data collection method used in this research are interview and documentation. The implementation of risk based audit Â in PT. Pupuk Kalimantan Timur started with the production of auditÂ plan, preliminary audit, auditing, and the audit report. The results indicated that risk based audit has been implemented well, although there are some aspects needs to be improved. The weakness of risk based audit is that the audit still depends on the risk management. While the strength of risk based audit is the audit were more focused on the work unit issues.Keywords: risk based audit, auditing, risk management